The Effect of Interactive Multimedia Use in Problem-Based Learning on Learning Outcomes - Muhammad Aldy Faturrohman; Basori Basori; Febri Liantoni (Journal of Informatics and Vocational Education, 2025)
The low learning outcomes and problem-solving abilities of vocational high school students in Banyudono in the subject of Informatics indicate the need for the application of more effective learning strategies based on interactive multimedia. This study aims to analyze the effect of problem-based learning (PBL) assisted by interactive multimedia on the Informatics learning outcomes of vocational high school students in Banyudono, given the limited empirical research that examines the integration of these two approaches in the context of regional vocational high schools. This study uses a quantitative approach with a quasi-experimental non-equivalent control group design. The sample was determined through proportional stratified random sampling involving experimental and control classes. Data were collected through pretest and posttest, then analyzed using normality test, homogeneity test, balance test, hypothesis test, and N-Gain test. The results showed that PBL learning assisted by interactive multimedia provided a significant improvement in learning outcomes compared to conventional learning. The average posttest score of the experimental class reached 85.45 and was higher than that of the control class, even though the pretest score of the control class was relatively higher. The N-Gain score of the experimental class was in the moderate to high category. These findings indicate that PBL assisted by interactive multimedia is effective in improving the learning outcomes of vocational high school students in Banyudono.